Synthesis of C-Ribosyl-1,2,3-triazolyl Carboxamides - Solarte, Carmen; Dos Santos, Michaël; Gonzalez, Simon; Miranda, Leandro S. M.; Guillot, Régis; Ferry, Angélique; Gallier, Florian; Uziel, Jacques; Lubin-Germain, Nadège (Synthesis, 2017)
Because of the emergence of new viruses, the need for new antiviral broad-spectrum compounds remains important. In this context, herein the synthesis of C-nucleosides, structurally close to ribavirin, a nucleoside presenting various biological activities and used until now particularly for its broad-spectrum antiviral properties, is reported. The compounds were designed in order to increase their stability and the number of hydrogen bond donor or acceptor in comparison to ribavirin, and to investigate the role of the carboxamide group on the biological activity. The efficient synthesis of 11 C-nucleosides is based on an indium-mediated alkynylglycosylation as the key step, followed by the construction of the triazole heterocycle. Amidation was performed with primary and secondary amines in yields up to 85%. An analogue nucleoside with a triazole without carboxamide group was also prepared in order to compare its activity. Finally, the carboxamide group was moved to the N-1 triazole position to mimic ribavirin.
Keywords: C-nucleosides; amidation; ribavirin; carboxamides; 1,2,3-triazoles